De autonijverheid in België - François Coppens; George Van Gastel (National Bank of Belgium, 2003)
– This paper provides an extensive overview of the economic importance and evolution of the car manufacturing industry. In addition, it provides evidence that the car industry is still playing a vital role in process innovation. The currently widespread lean production method, under which companies focus on their core activities and develop a network of subcontractors, in fact originates from the Japanese car industry. The introduction of the "lean production" concept in Europe had a far-reaching impact on corporate relations. Important responsibilities - such as product development, quality control, innovation efforts and timely deliveries - have been/are passed on to the subcontractors. Company clusters have been formed, which often also have consequences in terms of geographical location due to the necessity of "just-in-time" or even "just-in-sequence"-deliveries. The mere fact that global companies have implemented this production method, also adds to the internationalization of the subcontracting companies. The latter conclusion fuelled/fuels the trend to anchor as it were the industrial core activities through an appropriate policy. Such a policy must be based upon reliable statistical observations. A major disadvantage, however, is that because of their network structure, the corporate clusters' importance is hard to measure. Since the input-output tables are not available for the very latest years, on the one hand, and are not sufficiently detailed, on the other hand, a method has been searched for which allows to gauge the importance of a specific branch. In this paper the method will be applied to the car manufacturing in Belgium. The proposed calculation method is based on the supply and use tables drawn up by the Bank within the framework of the National Accounts Institute.
Keywords: C67; J21; L22; L62; R15; R34; 330; branch survey; car industry; subcontracting; indirect effects; Kfz-Industrie; Lean Production; Just in Time; Internationale Arbeitsteilung; Multinationales Unternehmen; Belgien